Pelatihan Pembuatan Sabun Cuci Piring Menggunakan Bahan Organik Di Desa Kedungbogo, Kecamatan Ngusikan - Sukma, Septi Ambar Indraningtia; Utsfiyul M, Nur Afifah; Cholilulloh, Wahyu David; Anggraeni, Nisa Lailatul; Haidar Ali, Muhammad; Larasati, Nadiah; Fatchulloh, H. Mohammad (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The utilization of natural ingredients in the manufacture of dish soap has enormous potential in improving the community's economy. Soap commonly used for washing is generally made from a mixture of lye and triglycerides from carbon chain fatty acids. In the process of making soap, the commonly used foamer is Sodium Lauryl Sulfate (SLS). The use of SLS causes skin irritation, both mild and severe skin irritation. With the presence of natural ingredients in the process of making dish soap, the resulting formulation can be environmentally friendly and does not contain SLS ingredients. One of the natural ingredients used is pandan leaves (Pandanus amaryllifolius), which have natural flavonoids, alkaloids, tannins, polyphenols, and saponins. The saponins in pandan leaves function to produce foam and have anti-bacterial substances. The purpose of this training is to provide learning in utilizing natural ingredients in the process of making dish soap. This training involves the active participation of community members in Kedungbogo Village, Ngusikan District, Jombang Regency, and is expected to become a business opportunity and improve the economy of the community in Kedungbogo Village, Ngusikan District, Jombang Regency.